Synergy between Graphene and Au Nanoparticles (Heterojunction) towards Quenching, Improving Raman Signal, and UV Light Sensing - Dalfovo, Maria Celeste (2014)
Here, we developed a simple method for obtaining a heterojunction composed of graphene (G) and surfactant-coated Au nanoparticles (NPs) to measure the film conductivity and surface enhanced Raman scattering (SERS). Monolayer G is obtained by chemical vapor deposition (CVD) and transferred via poly(methyl methacrylate) (PMMA) to microfabricated Au electrodes, glass, and silicon. Post-synthesis treatments of G with PMMA and ozone (O3) showed 1 and 6 orders of magnitude decrease in the conductivity, respectively. The heterojunction formation with Au NPs had no major effect on G conductivity. In this work is demonstrated that G quenches more than 90% of the combined photoluminescence and fluorescence of Au NPs and Rhodamine B (RhB), respectively. Signal quenching permitted quantitative analysis of SERS of RhB on various substrates including as-transferred graphene, oxidized graphene (OG), and the heterojunction. While G is mainly responsible for quenching photoluminescence and fluorescence, around 3 orders of magnitude increase SERS activity for RhB was accomplished by the heterojunction. Finally, we wanted to correlate changes in the current during UV light sensing experiments. We found striking differences in the sensing pro!les at different UV energies. KEYWORDS: graphene, nanoparticles, heterojunction, surface enhanced-Raman scattering, quenching, photoluminescence, and fluorescence.